Analisis Persepsi Mahasiswa Terhadap Peluang Bisnis di Sektor Digital - Mardikaningsih, Rahayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to evaluate the impact of higher education on students' readiness for digital business opportunities. The main findings show that students feel that the curriculum lacks practicality, and they emphasize the importance of practical experience and closer integration with industry. Students also criticized the lack of awareness of digital business trends and recommended more practical approaches, such as actual case studies and closer collaboration with companies. The results of this study provide important insights for higher education institutions to update their curricula, ensure students' engagement in practical experiences, and increase their awareness of digital business dynamics. In addition, collaboration with industry is crucial to ensure students are prepared for the challenges and opportunities that arise in this digital era. This research can serve as a foundation for policy and practice changes in higher education institutions, creating graduates who are more practically and conceptually prepared for the evolving business world.